Risk factors for Deliberate Self Harm in Bipolar Affective Disorder patients presenting to Tertiary care center- A cross-sectional study: Deliberate self harm in Bipolar affective disorders - Ganiger, Fakirappa B; Sharma, Manisha; Bijjal, Somashekhar (Nepal Journal of Neuroscience, 2022)
Abstract:- Background: Deliberate Self Harm (DSH) is a complex event, associated with psychosomatic, biological, social factors and psychiatric disorders. Current literature shows that, there is rise in DSH in psychiatric disorders and it has been recognised as major public health problem in India. So, objective of this study was to assess the underlying risk factors for DSH in patients with Bipolar Affective Disorder (BPAD). Methods: This cross-sectional study was conducted on 150 patients diagnosed with BPAD as per International Classification of Diseases; tenth revision (ICD-10). Semi-structured socio-demographic proforma was used to record basic profile. Deliberate self harm inventory (DSHI) was administered to assess the type of DSH. Young Mania Rating scale and Beck Depression Inventory were used to assess severity of symptoms. Results: Prevalence of DSH in present study was 33%. In socio-demographic profile, younger age group, lower education levels and being single were significant risk factors for DSH (p- value <.001, .016 and <.001 respectively) and among clinical variables, early years of disorder, severe mania, moderate and severe depressive episode in presence of medium to high suicidal intent, family history of mood disorders and co-morbid substance use and medical disorder were significant risk factors for DSH in BPAD with statistical significance (p<.0001). Conclusion: DSH is considered to be the significant predictor of suicide. BPAD is associated with high risk of DSH, which can be present in either depressive or manic episode. Patients with BPAD in early years of illness, should be evaluated thoroughly for risk factors, so that DSH risk can be minimised